The role of laparoscopy in the diagnosis of female infertility in material of the Department of Obstetrics and Gynaecology, Medical University of Łódź - Kowalczyk-Amico, Katarzyna; Szubert, Maria; Wierzbowski, Tomasz; Fras, Piotr; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2010)
Background: Laparoscopy is a useful tool in current fertility practice. Aim: The aim of this study was to evaluate the prevalence of different causes of infertility diagnosed by laparoscopy among women referred to the Department of Obstetrics and Gynaecology, Medical University of Łódź. Material and methods: One hundred and sixty-eight patients who were diagnosed laparoscopically in 2008 and 2009 were studied retrospectively. Frequency of the causes and findings were determined. Results: From the whole group of 285 women who underwent laparoscopy, 168 patients (59%) were diagnosed laparoscopically. Among this group 145 women (83%) were referred for the invasive diagnostic procedure due to primary infertility. The average age of primary infertile women was 30.8 years, secondary infertile women 32.6 years. Endometriosis was diagnosed in 113 patients (67%). Thirty-eight women (23%) were found to have a tubal disease; among these patients 36% had bilateral tubal blockage. Dense pelvic adhesions were more frequent in secondary infertile women. Adhesiolysis was conducted in 26% of examined patients. Conclusions: Diagnostic laparoscopy is a valuable technique for complete assessment of female infertility. Endometriosis is the most probable cause of infertility in two of three women. Other common factors responsible for infertility are tubal disease, adhesions and polycystic ovaries.